A comparative study on the investment value of residential property and stocks - Sun, Bing; Liu, Hongyu; Zheng, Siqi (International Journal of Strategic Property Management, 2010)
As real estate, residential property comprises not only the value of utilization, but also the value of investment, which is somewhat different from that of securities such as stocks and bonds. In this paper, the investment value of newly‐built residences and stocks are compared and analyzed theoretically and empirically. Firstly, the paper summarizes the diversity of costs, risks, and benefits of these two investments. Secondly, by quoting the quarterly price/rent indices on the housing market and that at the stock exchange in Shanghai, the paper explores the variances of these two investments with respect to their risk‐return characteristics from 1993 to 2003. Thirdly, the paper discusses the correlations between residential property price/rent index, property/general stock price index, and Consumer Price Index (CPI). Finally, by utilizing the Capital Asset Pricing Model (CAPM), the systematic and the unsystematic risks of these investments are segregated and compared with each other, based on a series of assumptions. The result suggests, on a quarterly basis, that residential property investment produces a higher risk‐adjusted return than that of general stock and property stock investment. Because of a weak/negative correlation between residential property and stock returns, residential property is an ideal candidate to be included into the stock investment portfolio. Moreover, residential property and property stock can be used as effective hedges against inflation. First Published online: 18 Oct 2010